An Advance Techniques of Computer Based Equipment Monitoring Structure in Open Cast Mines: Enhancing Efficiency and Monitoring in Open Cast Mines (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The state-of - the-art computing technology has development to the extent that there are many truck dispatching technologies that provide the ability to increase the efficiency of the truck and eventual savings. The installation of a dispatching device in a mine will yield operational advantages through minimizing processing times and achieving additional benefits by improved tracking, efficient routing and grade management. The performance of the utilized truck-shovel fleet based on the dispatch method in place, the nature of the truck-shovel network and a number of other factors. It is a typical circumstance in the mining industry that a substantial review of the possible strategies is carried out before shipping is carried out. In certain instances, machine imitation is the most appropriate efficient way of evaluating different dispatch approaches. The machine tracks the position and condition (full or zero, heading and speed) of each vehicle in the fleet. The program analyzes output figures, such as hauling roads, historical data on drive time to a given shovel spot, and loop time as long as it needs to make a round trip from the shovel to the dumpsite and returning.